Enhancing effects of Aloe vera gel extracts on the humoral and cellular immune response and growth performance in broiler chickens - Miah, Mohammad Alam; Akter, Snigda; Uddin, Md Saif; Sujan, Khaled Mahmud; Mustari, Afrina; Akter, Sharmin (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The experiment evaluated how Aloe vera gel (AVG) extract supplementation affected immune responses and physiological performances in broiler chickens. Materials and Methods: 90-day-old Cobb 500 broiler chicks were reared for 38 days without the addition of antibiotics, either through feed or water. At 10 days, chicks were allocated into three groups: A, B, and C (n = 30). Group A served as non-supplemented control. Groups B and C were administered aqueous extracts of AVG at 1.0% and 2.0%, respectively, with drinking water. Results: The supplementation of AVG potentiated the chicken immune response to Newcastle disease- vaccinated birds and sheep red blood cell-treated birds, which detected the highest antibody titers against Newcastle disease virus and sRBC. The cellular immune response evaluated through a cutaneous basophilic hypersensitivity test using phytohemagglutinin-P demonstrated a significant increase in skin thickness in AVG-supplemented birds. The relative sizes of lymphoid organs (bursa, spleen, and thymus) were significantly enhanced (p < 0.05) among the groups. Broilers given AVG-1 and AVG-2 exhibited significantly greater (p < 0.01) live body weight, dressing percentages, and serum protein and serum albumin levels. The supplemented groups experienced a significant reduction in total serum cholesterol, triglycerides, and low-density lipoprotein–cholesterol values, while the levels of high-density lipoprotein-cholesterol remained unchanged. The dietary aqueous extracts of AVG are effective in enhancing innate and specific immunity. Conclusion: This work strengthens the perspective of the use of AVG as an immune stimulant to facilitate recovery from immune suppression states, enhance innate and specific immunity, and improve broiler growth performance. Adv. Vet. Anim. Res., 11(1): 40-46, March 2024 http://doi.org/10.5455/javar.2024.k745